A Pilot Study of the User Experience in an Augmented Reality Mobile App to Support Teaching of Hematology - Soares, Jizar M. Vorma; Fernandes, Diógenes P.; Stefani, Cassiano J. Mandelli; Santiago, Pablo; Zanatta, Alexandre L.; Rieder, Rafael (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
This paper presents the development and pilot study of the user experience of the AnemiaAR Mobile App, an Augmented Reality serious game to support teaching of hematology. We created two versions of the game: marker-based (using Vuforia resources) and markerless (using MRTK resources). Our counterbalanced study considered assessing the two app versions by 12 volunteers, Medicine undergraduate students, enrolled in a hematology course. At the post-test, the subjects answered the User Experience Questionnaire (UEQ) and responded to an interview about the strengths and weaknesses of each version. The results showed 17 of the 26 UEQ aspects with better evaluation means for the markerless support, suggesting a more positive user experience for this version. This panorama is corroborated by the subjective interview data, showing a user preference for markerless interaction for this AR mobile game.